CUSTOMER ENGAGEMENT DI MARKETPLACE: STUDI KASUS PADA SHOPEE LIVE DAN KEPUTUSAN PEMBELIAN ULANG - Deni Marsha; Erick Karunia; Syahran Syahran; Aswan Aswan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of customer engagement through the Shopee Live feature on repurchase decisions. In the digital era, live commerce has emerged as a new medium for creating real-time interactions between sellers and buyers. Using a quantitative approach, data were collected through an online questionnaire distributed to 100 active Shopee users who had made purchases via Shopee Live. The analysis was conducted using multiple linear regression to examine the effects of interactivity, trust in the host/seller, and satisfaction with the live shopping experience on repurchase decisions. The results show that the three independent variables simultaneously have a significant effect on repurchase decisions, with an adjusted R² of 0.604. Partially, trust and satisfaction have significant effects, while interactivity does not. These findings imply that consumer loyalty in live streaming commerce is more strongly influenced by trust and experience than by interaction alone.